Vehicle impact exercises in the development of some mental skills for junior basketball - Hurr, Sahar (Journal of Physical Education, 2010)
The research contains four sections : Section one : the definition of the research . Basketball game considers as one of group games which depends basically on the players basic skills in order to be able to add excitement to the game , this skill needs to go on training specially four young in order to reach the right technique which reduce the work . The mental skills have a big role in doing the skill which we must develop it and do not neglect it by the hainers because the mental skills consider as the first step to show the skill .The exciting thing appears in the outer environment . The importance of this research is shown in using the compound trainings in developing some of young player’s mental skills in basketball . The problem : The problem of the research is that , the most coaches neglect the mental and basic skills and they interest in the physical and skill sides . The Two aims : 1. make compound trainings to develop some of the mental skills for the young in basketball . 2. Knowing the effect of compound trainings in developing the mental skills to the young in basketball . Supposition of research : - there is an effect in the compound trainings in developing some of the mental skills for the young in basketball . The fields of the research : 1. The human field :10 players from Al-Karkh clup under 16 years . 2. The time field : the time period from 22/ 5/ 2008 until 11/8/2008 . 3. The place fields : the ball of Al-Karkh club / Baghdad . Section two : The method of research and its fields procedures . The research used experimental method and followed the design of two groups . The sample of the research was the young players of Al-Karkh club basketball under 16 years ( 10 players ) . The players are chosen dependently and they divided into two groups . The before experiment is applied to the sample of research in 14/6/2008 and the work with experiment began from 5/6/2008 until 7/8/2008 , the period was 8 weeks with three training units a week and the training units were 24 . Section three : The presentation , analyzing and discussion of the results : In this section the results of walkuksen and man witting tests (before and after) are shown , as well as the discussions of results . Section four : Conclusions and recommendations : - Conclusions : according to the results that has been reached , the researcher concluded the following : 1. We should depend on the compound trainings in the schedules to the young in basketball . 2. We should be care with compound trainings because they help in developing some of the mental skills . 3. We should be care with mental training and do the mental skill tests regularly . 4. It is necessary to have a specialist in psychology with our national teams to take a part developing and improving the mental and psychological situation for the players